Lespratiques funéraires en Pannonie de l'époque Augusteenne à la fin du 3e siècle texte et cartes - Márton, András 1976- (Archaeopress Publishing Ltd., 2019)
This volume aims to give an overview of Roman burial practices in Pannonia during the Early Roman period through the study of tomb structure, the selection and treatment of grave goods and analysis of human remains. It proposes a synthesis of the published finds to serve as a base for future research in the region
Titel der Dissertation: "Le rituel funéraire en Pannonie de l'époque augustéenne à la fin du 3e siècle en comparaison avec les provinces occidentales"
Keywords: Geschichte 50 v. Chr.-300; Burial / Pannonia; Funeral rites and ceremonies / Pannonia; Excavations (Archaeology) / Pannonia; Bestattungsritus; Bestattung; Pannonia / Antiquities, Roman; Pannonien; Hochschulschrift